Information Technology Usage By Enterpreneurs: A Technology Acceptance Model (TAM) Study Of The Usage Pattern, Usage Determinants And The Moderating Impact Of Entrepreneur's Traits - Nelson, Olunna Ndubisi (2002)
Much previous research has established that perception such as perceived usefulness and ease of use are important factors influencing the use of information technologies. Similar amount of work has been directed to investigate the determinants of perception, for example, organizational factors, environmental factors, system characteristics, etc. but very often neglected, are the unique traits of users or user groups. Using the Technology Acceptance Model (TAM), the current research examines the IT usage pattern of Malaysian entrepreneurs, the influence of perceived usefulness and perceived ease of use on IT usage, the determinants of perceived usefulness and ease of use, and the moderating impact of entrepreneur's traits such as innovativeness and perseverance on the relationship between perceived usefulness, ease of use, and usage. User traits and technology usage were studied among one hundred and seventy seven members of the National Association of Malaysian Women Entrepreneurs (NAWEM) and members of the Entrepreneur Development Unit of the Malaysian prime Minister's Department. The study found validity for many of TAM contructs among Malaysian entrepreneurs. IT usage was influenced by perceived usefulness. Perceived ease of use has influence on usage indirectly via perceived usefulness. There is no direct relationship between ease of use and usage. Prior computer experience, computing training, staff support, and technical support were found to influence perceived usefulness. Perceived ease of use was influenced by technical support, training, staff support, data intensity, and stakeholders influence. Innovativeness and Perseverance were found to moderate the impact of perceived usefulness and perceived ease of use respectively on IT usage. This research provides the basis for the integration of innovativeness and perseverance into the technology acceptance model. The resulting model is termed the Entrepreneur's Technology Acceptance Model (ETAM).